2021
DOI: 10.1111/medu.14464
|View full text |Cite
|
Sign up to set email alerts
|

Invoking culture in medical education research: A critical review and metaphor analysis

Abstract: Introduction: 'Culture' is a word frequently invoked within medical education literature to explain challenges faced by learners in practice. While social settings and practices are widely acknowledged as critical influences on medical education, there is vast variability in how the term 'culture' is employed. This may lead to confusion, resulting in assumptions and oversights.Objective: This critical literature review aims to characterise how the term 'culture' is explicitly and implicitly conceptualised in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…They found that there is a 'notable absence around conceptualisations of culture that allow educators, students and administrators agency' but at the same time acknowledge the influence of social settings and practices. 19 Watling et al offer a framework that recognises three perspectives on culture: organisational, identity and practice. 9 The organisational perspective highlights the shared assumptions and values that bind individuals within an organisation.…”
Section: The Emergent Dialoguementioning
confidence: 99%
See 2 more Smart Citations
“…They found that there is a 'notable absence around conceptualisations of culture that allow educators, students and administrators agency' but at the same time acknowledge the influence of social settings and practices. 19 Watling et al offer a framework that recognises three perspectives on culture: organisational, identity and practice. 9 The organisational perspective highlights the shared assumptions and values that bind individuals within an organisation.…”
Section: The Emergent Dialoguementioning
confidence: 99%
“…What is now emerging is an interest in the impact of the wider organisation in which a trainee and a supervisor are situated, how this impacts on learning and how this varies across health services, cities, regions and countries. As part of exploring these institutional factors, a critical review by Bearman et al is timely in its invitation to medical educators to ‘invoke culture’ 19 . Their work revealed that medical educators comment on culture frequently but usually negatively or from a neutral stance.…”
Section: The Emergent Dialoguementioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent literature, including Bearman et al's contribution in this issue, underscores the imperative by exploring the relationship between culture, values, narrative and medical education. [2][3][4][5] Culture is a contested concept, but it influences pedagogy, teaching and learning, 2,3,5 so there is a compelling case for further research and theory development to bring about a better understanding of culture with its concomitant values and narratives both in medical education and healthcare writ large. Justice, prudence and fortitude or courage are thought to be chief among the values that enable people to flourish, experience joy and find fulfilment.…”
mentioning
confidence: 99%
“…There are gaps in medical education that have been subject to little or no critical scrutiny 1 . Recent literature, including Bearman et al’s contribution in this issue, underscores the imperative by exploring the relationship between culture, values, narrative and medical education 2‐5 . Culture is a contested concept, but it influences pedagogy, teaching and learning, 2,3,5 so there is a compelling case for further research and theory development to bring about a better understanding of culture with its concomitant values and narratives both in medical education and healthcare writ large.…”
mentioning
confidence: 99%